Hubungan antar Kualitas Kehidupan Kerja, Sinergi Kantor-Rumah, Kepuasan Kerja, dan Kinerja - Nikodemus Hans Setiadi Wijaya; Prastyaningtyas Prabandari (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
This study aims at investigating the links among quality of work life, synergy of office-home, job satisfaction, and employee performance. One hundred and two (102) respondents working in urban villages in Depok Sub Districts in DIY (Yogyakarta Special District). Results of the study found that quality of work life and synergy of office-home were positively related to employee performance. The variables were also positively related to job satisfaction. Furthermore, job satisfaction was positively related to employee persormance. It was found that job satisfaction mediated the effects of quality of work life and synergy office-home on employee performance.